Pengembangan Permainan Labirin untuk Membantu Perkembangan Motorik Anak - Graficha Aryudhetika Kusuma (Program Studi Teknik Elektro Universitas Khairun, 2016)
Labyrinth an astound as a mind-boggling fanning street and has a great deal of stalemate which is regularly used to create motoric children, sharpen the capacity of kids to know the spaces, pathways through which to decide an area inside the labyrinth brought together entirety. In the garden of youth lesson, picture formed labyrinth just on paper and in making a way utilizing a pencil part of the picture there is less once recoloring. For this situation the enthusiasm for the tyke's enthusiasm for adapting less. Consequently, it requires new development a labyrinth diversion to premium youngsters in taking in the labyrinth. Multiplatform based instructive amusement planned to utilize SDLC (System Development Life Cycle) and assembled utilizing the Unity 3D, Blender 3D, Android SDK and Photoshop. This maze game breezed through the test with a questionnaire got from exhibiting this maze game in early youth and kindergarten. Aftereffects of the study were taken from poll information, there are around 90% of children preferred the look and the kid's enthusiasm for learning maze in instructive diversions.